Bioinspired ultrasound-driven ultrafast soft microgripper - Chengxi Zhong; Vincent Winderoll; Khemraj Gautam Kshetri; Cornel Dillinger; Tommaso Bianchi; Zhan Shi; Justus Schnermann; Marco Amabili; Song Liu; Raphael Wittkowski; Nitesh Nama; Daniel Ahmed (Proceedings of the National Academy of Sciences, 2026)
Understanding how acoustic waves interact with soft matter is critical for developing new strategies for dynamic control, actuation, sensors, and manipulation at small scales. A major challenge in soft matter and microrobotics is how to achieve fast, precise, and remotely controlled actuation at the microscale without sacrificing compliance or biocompatibility. Here, we introduce wireless artificial microcilia based on acoustically activated soft hydrogel microstructures inspired by Venus flytrap and vorticella . The structures, termed SonoGrippers, consist of dual microcilia (≤120 µm length) with outward-facing sharp tips. Upon acoustic excitation, SonoGrippers deliver ultrafast (~2 ms), reversible, and controllable actuation, enabling remote attraction, gripping, and release of objects. By tuning structural designs and acoustic parameters, SonoGrippers exhibit diverse deformation modes and tunable response dynamics, allowing adaptable gripping performance across various application scenarios. Proof-of-concept demonstrations with stationary and mobile biological samples confirm their robust functionality. Combining simple fabrication, additive-free operation, wireless rapid control, and biocompatibility, SonoGrippers provide a promising platform toward next-generation biomedical manipulation, soft microrobotics, and bioengineering applications.